Thermal and hydraulic characteristics of a parabolic trough collector based on an open natural circulation loop: The effect of fluctuations in solar irradiance. (August 2022) - Balasubramanian, K.R.; Jinshah, B.S.; Ravikumar, Kottala; Divakar, S.
Graphical abstract: Highlights: The novel Parabolic Trough Collector is based on an Open Natural Circulation loop. New methodology correlates actual solar data to input for an inhouse test facility. Based on the application, the system suits for hot water as well as steam generation. The system generates 8.7 kg of steam/ hot water at 97.5?C per day. The developed system has better economic benefits in rural agro-industries. Abstract: This study introduces a novel open natural circulation loop-based parabolic trough collector capable of operating in dual-mode and is tested experimentally for four days of solar insolation under three common climatic conditions. The tests are conducted in two modes viz hot water and low enthalpy steam generation. Both modes shows stable thermo-hydraulic characteristics with Start-up oscillations. Hot water mode experienced single mode thermal oscillations with 0.015 Hz having a decay ratio of 0.45. Steam generation mode experienced little fluctuation in outlet temperature with the insolation. However, it affects mass flux in both modes. Nevertheless, all fluctuations are stable and die out faster. Type-I instability is observed in two-phase flow transition in the receiver tube for both the modes. Overall efficiency is estimated at 68%, which is almost consistent throughout the day. The efficiency and total heat loss are also observed to be dependent on total insolation. In Hot water mode, the system can produce 150 L of hot water at 97.5 °C, and 8.7 kg of total steam in Steam generation mode. The results also show that proposed Parabolic Trough Collector based on Open natural Circulation loop is suitable for agricultural and small-scale industries where hot water or low-enthalpy steam at temperatures of 80–110 °C are required.